Peran Guru PJOK dalam Meningkatkan Minat Belajar Penjaskes di SMP Negeri 7 Kota Sungai Penuh - Maizan, Inggar; Trishandra, Jonika; Heliza, Romiya (Jurnal Muara Olahraga, 2025)
Abstract This study aims to see how the Role of Physical Education Teachers in Increasing Interest in Learning Physical Education at SMP Negeri 7, Sungai Penuh City. The research data used qualitative descriptive data obtained through interviews with Physical Education Teachers and students of SMP Negeri 7 Sungai Penuh City who were the source of observations or data regarding interest in learning Physical Education at SMP Negeri 7 Sungai Penuh City. The results of the study indicate that the implementation of the role of teachers at SMP Negeri 7 Kota Sungai Penuh is good overall. The results of the study on the Role of Teachers in Increasing Interest in Learning Physical Education at SMP Negeri 7 Kota Sungai Penuh are that the role played by teachers in their duties is carried out well and several factors in the implementation of learning such as students feeling less understanding of the material and lack of student attention regarding the implementation of learning both in the form of material or practice. So that the overall results between the interrelationships of the roles of Physical Education Teachers are included in the good category in their implementation because they have maximized the learning process at SMP Negeri 7 Kota Sungai Penuh.